MR imaging of the arterial vessel wall: Molecular imaging from bench to bedside - Makowski, Marcus R.; Botnar, Rene M. (Radiology, 2013)
Cardiovascular diseases remain the leading cause of morbidity and mortality in the Western world and developing countries. In clinical practice, in vivo characterization of atherosclerotic lesions causing myocardial infarction, ischemic stroke, and other complications remains challenging. Imaging methods, limited to the assessment luminal stenosis, are the current reference standard for the assessment of clinically significant coronary and carotid artery disease and the guidance of treatment. These techniques do not allow distinction between stable and potentially vulnerable atherosclerotic plaque. Magnetic resonance (MR) imaging is a modality well suited for visualization and characterization of the relatively thin arterial vessel wall, because it allows imaging with high spatial resolution and excellent soft-tissue contrast. In clinical practice, atherosclerotic plaque components of the carotid artery and aorta may be differentiated and characterized by using unenhanced vessel wall MR imaging. Additional information can be gained by using clinically approved nonspecific contrast agents. With the advent of targeted MR contrast agents, which enhance specific molecules or cells, pathologic processes can be visualized at a molecular level with high spatial resolution. In this article, the pathophysiologic changes of the arterial vessel wall underlying the development of atherosclerosis will be first reviewed. Then basic principles and properties of molecular MR imaging contrast agents will be introduced. Additionally, recent advances in preclinical molecular vessel wall imaging will be reviewed. Finally, the clinical feasibility of arterial vessel wall imaging at unenhanced and contrast material-enhanced MR imaging of the aortic, carotid, and coronary vessel wall will be discussed. © RSNA, 2013.
CRIS-Team Scopus Importer:2023-03-08